Evidence of inappropriate cardiovascular risk assessment in middle-age women based on recommended cut-points for waist circumference - Florath, Ines; Brandt, S.; Weck, M.; Moss, A.; Gottmann, P.; Rothenbacher, D.; Wabitsch, M.; Brenner, H. (Elsevier, 2014)
© 2014 Elsevier B.V. Background and aims: Diverse waist circumference thresholds for assessment of metabolic and cardiovascular risk in Caucasians are recommended by different health professional organizations. We aimed to determine optimal sex-specific thresholds for anthropometric measures showing the strongest association with cardiovascular risk factors in a cohort of middle-aged Germans. Methods and results: Statistical analyses are based on data from 426 mothers and 267 fathers of participants of the Ulm Birth Cohort Study undergoing a clinical follow-up examination in 2008 (median age 41 years) using logistic regression analyses. The prevalence of many cardiometabolic risk factors was significantly higher in men than in women; hypertension: 45%/17% ( p<0.0001), apolipoprotein ratio B/A1>0.72: 35%/9% (<0.0001), hyperglycemia: 11%/14% ( p=0.3), which is in contrast to the predicted cardiovascular risk of 52%/70% and 24%/36% based on thresholds for waist circumference proposed by International Diabetes Federation and American Heart Association, respectively. We determined optimal thresholds for waist circumference between 90 and 95cm for men and women. Using a threshold of 92cm the prevalence of abdominal obesity was 59% in men and 24% in women, which was in agreement with the higher prevalence of overweight and obesity in men than in women (Body Mass Index (BMI)>25: 64%/35%). The prediction of cardiometabolic risk factors by waist circumference and waist-to-height ratio did not outperform the prediction by BMI. In contrast to BMI, waist circumference was correlated with body height independent of sex. Conclusion: Currently proposed thresholds for waist circumference spuriously overestimate the cardiovascular risk in women, but not in men in a German population.